The FMRpolyGlycine Protein Mediates Aggregate Formation and Toxicity Independent of the CGG mRNA Hairpin in a Cellular Model for FXTAS - Hoem, Gry; Bowitz Larsen, Kenneth; Øvervatn, Aud; Brech, Andreas; Lamark, Trond; Sjøttem, Eva; Johansen, Terje (Frontiers in Genetics, 2019)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disorder caused by a CGG-repeat expansion in the 5’ UTR of the FMR1 gene on the X-chromosome. Both elevated levels of the expanded FMR1 mRNA and aberrant expression of a polyglycine protein (FMRpolyG) from the CGG-repeat region are hypothesized to trigger the pathogenesis of FXTAS. While increased expression of FMRpolyG leads to higher toxicity in FXTAS models, the pathogenic effect of this protein has only been studied in the presence of CGG-containing mRNA. Here we present a model that allows measurement of the effect of FMRpolyG-expression without co-expression of the corresponding CGG mRNA hairpin. This allows direct comparison of the effect of the FMRpolyG protein per se, versus that of the FMRpolyG protein together with the CGG mRNA hairpin. Our results show that expression of the FMRpolyG, in the absence of any CGG mRNA, is sufficient to cause reduced cell viability, lamin ring disruption and aggregate formation. Furthermore, we found FMRpolyG to be a long-lived protein degraded primarily by the ubiquitin-proteasome-system. Together, our data indicate that accumulation of FMRpolyG protein per se may play a major role in the development of FXTAS.